Analisis Kimia dan Sifat Antibakteri Sabun Transparan Berbasis Minyak Kelapa Sawit dengan Penambahan Ekstrak Mikropartikel Gambir - Neswati Neswati; Sahadi Didi Ismanto; vioni derosya (Universitas Djuanda, 2019)
Gambir extract microparticle is adding the value of palm oil-based transparent soap. Catechin content from extract gambir has the antibacterial activity to Staphylococcus aureus. As microparticle, extract gambir can be absorbed well into skin pore when applied as one of transparent soap contents. Thus, this research aimed for obtaining information related to the optimum concentration of extract gambir in microparticle, based on chemical characteristic and antimicrobial. Gambir was locally obtained from Pangkalan, 50 Kota District, West Sumatera. Gambir was diluted in ethanol then ultrasonified in order to get gambir as microparticle. There were 8 treatments and duplicated which were 3%, 4%, 5%, 6%, 7%, 8%, 9% and 10% of gambir extract addition. From this study, the optimum addition of gambir extract was 5% with 26.11% of water and volatile content, 1.0823% was insoluble in ethanol, 0.96% of free fatty acid, 46.48% of fatty acid, 13.86% unsaponifiable fraction, and the inhibition zone diameter of Staphylococcus aureus was 36.6 mm.